Frames of Domination: Connecting the Chaining of Aboriginal 'Prisoners' and Settler Emotions, 1900-1950 - Clewett, Elizabeth Megan Kiemel (Culture and History: Student Research Papers, 2024)
From the establishment of the first Australian colony until the mid-1900’s, Aboriginal people were routinely forcibly restrained using chains by white settlers. Using two lenses, this article analyses a selection of photographs published in colonial newspapers, depicting this practice. It firstly examines how colonial photography constructed the Aboriginal body as an object of fear to be controlled by the frightened settler. This article also interrogates how these photographs appealed to humanitarian sympathies, which themselves were highly conditional, with comparisons to slavery embodying a ‘safe’ method of critique, one which did not challenge the settler colonial state.